AMALAN PENGGUNAAN BAHAN BANTU MENGAJAR (BBM) MENERUSI PENGINTEGRASIAN KEMAHIRAN BERFIKIR ARAS TINGGI (KBAT) DALAM KALANGAN GURU PENDIDIKAN ISLAM SEKOLAH RENDAH NEGERI PERAK: THE PRACTICES OF USING TEACHING AIDS (BBM) THROUGH AN INTEGRATION OF HIGHER ORDER THINKING SKILLS (KBAT) AMONG ISLAMIC EDUCATION TEACHERS IN PRIMARY SCHOOLS IN PERAK - Othman, Mohd Syaubari; Kassim, Ahmad Yunus (Journal of Islamic Educational Research, 2017)
This study aims to identify the practices of using teaching aids (BBM) among Islamic Education teachers in the teaching and learning process (PdP) based on Higher Order Thinking Skills (KBAT). This study was conducted in eight primary schools in Perak involving interviews with teachers of Islamic Education (GPI), headmasters, assistant headmasters and students. Components of teaching aids (BBM) are viewed through three main components which are Pattern Routine, Pattern Ancillary and Non-Pattern through the integration of teaching and learning which involves KBAT based on the elements of application, analysis, evaluation and invention. The results of the interview are governed by N'vivo Version 7 software to produce a matrix table theme and related practices of BBM among GPI of primary schools in Perak based on KBAT. The results show that there are 12 types of BBM used in the GPI's PdP with different pattern used. Much emphasis is given to the Pattern Routine while Pattern Ancillary and Non-Pattern just become the support material in the KBAT-based of PdP. The Pattern Routine consists of textbook, LCD computer, whiteboard and A4 paper while the Ancillary consists of handout (manila cards), mahjong paper, reference books and scan card. The Non-Pattern consists of newspapers, charts, films and radio cassette.